Ahmet Yesevî Studies in Kyrgyzstan - İSLAMOĞLU, Abdülmecit (Scientific Journal of Faculty of Theology, 2020)
Hodja Aḥmad Yasawī is a significant figure having a valuable effect on Kyrgyzs who are important community in the Middle Asia from his age to our time. His hikmets are regarded as sacred relics passed down from generation to generation among Kyrgzs. In this paper, the studies are analysed in form of book, article and report about Aḥmad Yasawī and his sect, namely, Yasawiyya which is regarded as an important value in terms of the fight of independence andsafeguarding their national identity throughout history. In these studies, issues mentioned include the life of Aḥmad Yasawī, his mystic character, world of thought, text and content of his hikmets, their effects on Turkish language and literature, Aḥmad Yasawī’s effect on Kyrgyzs and his place in the Kyrgyz culture. Another issue which attracts attention in a substantial part of these studies is defending the opinion that Aḥmad Yasawī was born in Cazı/Özkent.